Out of range ebook - Box, C. J. (Joe Pickett, 2006)
Wyoming game warden Joe Pickett is about to become the hunted in this suspenseful thriller in the #1 New York Times bestselling series. When a good friend and fellow warden kills himself, Joe Pickett is chosen to temporarily run his Teton district. But Jackson, Wyoming, is a far cry from Joe's hometown of Saddlestring—and it doesn't help that now Joe feels compelled to investigate  the circumstances surrounding his friend's suicide. But as he comes closer to the truth, the more his own life spirals out of control—and he realizes if he isn't careful, he may be Jackson's next victim...